2018
DOI: 10.1007/s11669-018-0635-2
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibria of the Ti-Al-Nb System at 1000, 1100 and 1150 °C

Abstract: 1000, 1100 and 1150°C isothermal sections of the Ti-Al-Nb system were studied using x-ray diffraction, scanning electron microscopy and electron probe microanalysis. A small island-like region of single b 0 is present at 1000, but absent at 1100 and 1150°C. c 1 is not a stable phase at 1000 and 1150°C. Three three-phase fields (a 2 ? b 0 ? r, b 0 ? r ? c and a 2 ? b 0 ? c) are identified in the 1000°C isothermal section (30-60 at.% Ti content). The 1100°C isothermal section is firstly studied completely. It in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 35 publications
(60 reference statements)
4
19
0
Order By: Relevance
“…Based on the above experimental results, the polythermal section in the Ti-Al-Nb ternary system covering the composition range of 30-78 at.% Ti was established and is illustrated in Figure 7. The experimental data in this work are highlighted in red and compared with some reported ones from the literature [17,21,22]…”
Section: Polythermal Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the above experimental results, the polythermal section in the Ti-Al-Nb ternary system covering the composition range of 30-78 at.% Ti was established and is illustrated in Figure 7. The experimental data in this work are highlighted in red and compared with some reported ones from the literature [17,21,22]…”
Section: Polythermal Sectionmentioning
confidence: 99%
“…Due to the lack of thermodynamics data and phase equilibria, their results are questionable. In 1995, Miracle Metals 2020, 10, 871 2 of 15 et al [20] obtained a partial polythermal section of Ti-22Al, but the Ti-Al boundary and the O phase region of the polythermal section are quite different from those reported later [21,22]. For example, Muraleedharan et al [23] found that the upper temperature limit for the stability of the O phase is about 1000 • C. Above 1000 • C, the O phase disappears.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Phase diagrams of the three constituent binary systems in the Ti-Al-Nb system-Ti-Al [24], Al-Nb [25], and Ti-Nb [26]-have been sufficiently delineated. The isothermal sections at 1000 • C [27][28][29][30], 1100 • C [30,31], 1150 • C [28][29][30], 1200 • C [27,32], 1300 • C [33], and 1400 • C [28,29,34,35] from experimental data are available in the literature. In addition, isopleth sections show the development of phase equilibria, such as the Ti 72.5 Al 27.5 -Nb [36], Ti 78 Al 22 -Nb [37], TiAl-TiNb [37,38], 45Al [25], 47Al [25], 8Nb [25,39], and 10Nb sections [39].…”
Section: Introductionmentioning
confidence: 99%
“…Phase diagrams of the three constituent binary systems in the Ti-Al-Nb system-Ti-Al [24], Al-Nb [25] and Ti-Nb [26]-have been sufficiently delineated. The isothermal sections at 1000 °C [27][28][29][30], 1100 °C [30,31], 1150 °C [28][29][30], 1200 °C [27,32], 1300 °C [33], and 1400 °C [28,29,34,35], from experimental data, are available in the literature. In addition, isopleth sections show the development of phase equilibria, such as the Ti72.5Al27.5-Nb [36], Ti78Al22-Nb [37], TiAl-TiNb [37,38], 45Al [25], 47Al [25], 8Nb [25,39], and 10Nb sections [39].…”
Section: Introductionmentioning
confidence: 99%